Designing a basic income guarantee for Canada - Robin W. Boadway; Katherine Cuff; Kourtney Koebel (Queen's University, Department of Economics, 2016)
We propose mechanism for implementing a two-stage harmonized Basic Income Guarantee with federal and provincial components. In Stage One, the federal government replaces its refundable and nonrefundable tax credits with an income-tested basic income delivered through the income tax system. The reform is revenue-neutral. In Stage Two, each province decides whether to implement a provincial basic income guarantee that is harmonized with the federal one but allows province-specific basic income levels. The provincial basic income replaces provincial refundable and nonrefundable tax credits as well as welfare and disability transfers, and is also revenue-neutral. All social services and contributory social insurance programs remain intact. An illustrative calculation using Statistical Canada's SPSD/M model shows the financial feasibility of a national BIG of 20,000 per adult adjusted for family size with a benefit reduction rate of 30%.
Keywords: H2; H7; I3; 330; basic income guarantee; inequality; fiscal federalism